SYSTEMATIC AND STRUCTURAL DEVELOPMENT OF THE INDUSTRY OF UKRAINE: STATE AND PRIORITIES FOR IMPROVEMENT - SKYBA, Halyna; KORBUT, Sergey; SHAPOVALOVA, Inga (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study draws attention to the problems of functioning and development of industry as a type of economic activity in Ukraine. The purpose of the study is to carry out a system-structural analysis and justify on this basis priorities for improving the parameters of the development of the industry of Ukraine. The strategic priorities of the state policy of realizing the potential of industry in the economy of Ukraine have been determined. It was concluded that the intensification of processes of restoration of potential and ensuring the systemic and structural development of Ukrainian industry requires the convergence of institutional support (with EU countries) for the development and implementation of structural reforms of the national economy. The main directions and means of convergence of institutional support and structural reform of the industry of Ukraine are indicated. It was concluded that the lack of formation of effective approaches to the organization of the state policy of managing the development of the industry of Ukraine requires the development of an adequate toolkit for stimulating the relevant processes as a strategic driver of the implementation of structural reforms and the formation of processes of expanded reproduction of the domestic industrial sector. The applied value of the research results lies in the determination of strategic priorities and means of state policy for stimulating the development of Ukrainian industry at the current crisis stage of its development. The scientific novelty of the research results lies in the further development of the methodology for substantiating priorities and means of sectoral development and ensuring effective institutional reforms and structural changes in the system of the national economy.
Keywords: sectoral policy; industry; system reforms; sectoral development policy; priorities of state regulation; improvement of the structure of the national economy